Managers of innovation : insights into making innovation happen - Storey, John; Salaman, Graeme (U.S.A. : Blackwell Publishing, 2005)
This book looks at how to foster innovation in organizations, focusing on managers as the key participants in the process. * Presents an original theory about the characteristics of managers in "good innovative organizations" and "poor innovative organizations.
Part I : Introduction -- 1. Innovation : problems and possibilities -- 2. The Current state of knowledge about innovation -- Part II: Managers accounts of innovation -- 3. From tight control to the edge of anarchy: managing innovation in telecommunications -- 4. Managing creative workers in an innovative way -- 5. Contrasting approaches to innovation in engineered manufactured goods -- 6. Innovation in the voluntary sector -- Part III: Synthesis -- 7. Conclusions
Includes bibliographical references and index.
Keywords: TECHNOLOGICAL INNOVATIONS; TECHNOLOGICAL INNOVATIONS -- MANAGEMENT